2018
DOI: 10.1007/s00330-017-5274-1
|View full text |Cite
|
Sign up to set email alerts
|

What are the predictors of clinical success after percutaneous vertebroplasty for osteoporotic vertebral fractures?

Abstract: • Performing vertebroplasty within 2 months following a fragility fracture increases success rate. • Presence of an intravertebral cleft at baseline is a predictor of poor mid-term outcome. • A pre-intervention MRI should be performed to ascertain the indication of vertebroplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…Predictive factors of a favorable outcome included an early procedure (performed within 2 months after fracture) and the absence of intravertebral cleft on preintervention imaging. 32 The results of the various randomized trials are apparently contradictory. However, these trials differ in many methodological aspects.…”
Section: Efficacy Of Vertebral Augmentation Techniques On Pain In Ostmentioning
confidence: 99%
“…Predictive factors of a favorable outcome included an early procedure (performed within 2 months after fracture) and the absence of intravertebral cleft on preintervention imaging. 32 The results of the various randomized trials are apparently contradictory. However, these trials differ in many methodological aspects.…”
Section: Efficacy Of Vertebral Augmentation Techniques On Pain In Ostmentioning
confidence: 99%
“…Despite controversies about the efficacy of routine percutaneous vertebroplasty (PVP) [6][7][8] in symptomatic OVCFs, PVP remains a commonly used tool in this indication, allegedly providing vertebral stability and thus potentially improving the clinical outcomes [9], especially when performed at the acute phase [10,11]. However PVP appears insufficient to correct the structural deformities (vertebral height loss and kyphotic angulations) and, in unstable OVCFs (grade A3 in Magerl's classification [12]), might cause bony fragments bulging into the spinal canal.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, previous studies found twenty-one percent of vertebrae had new areas of marrow edema on follow-up. Twenty-two percent of vertebrae imaged 6 months after vertebroplasty had moderate or severe edema, progressive and persistent edema and interval height loss after successful vertebroplasty are common 39 . The models were designed to simulate physiological movements such as flexion, extension, lateral bending, and twisting with different loads, in order to explore the stresses of adjacent and distal non-treated vertebrae.…”
Section: Discussionmentioning
confidence: 99%